2014
DOI: 10.1016/j.foodcont.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two antimicrobial packaging films against Escherichia coli O157:H7 strains in vitro and during storage of a Spanish ripened sheep cheese (Zamorano)

Abstract: The antimicrobial activity of two packaging films (polypropylene-PP-and polyethylene terephthalate-PET-) coated with different concentrations (0, 4, 6 and 8%) of essential oil from Origanum vulgare (OR) and Ethyl Lauroyl Arginate HCl (LAE) was tested against two E. coli O157:H7 strains using in vitro systems and a raw milk sheep cheese model (Zamorano). The influence of the antimicrobials on the sensory attributes of cheese was also evaluated. For both strains, the MBC (minimum bactericidal concentration) valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 25 publications
1
32
0
1
Order By: Relevance
“…One major drawback of essential oils molecules is their volatile nature; therefore, the main applicative methodology for their incorporation into polymers is by coating technologies. [18,19] Once the essential oils are directly incorporated into the polymer matrix by high-temperature melt processing, antimicrobial activity is achieved. [16,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] However, this activity is evaluated, in most cases, immediately after film production, [29,[33][34][35] while the challenges associated with the controlled and prolonged activity of these films are not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…One major drawback of essential oils molecules is their volatile nature; therefore, the main applicative methodology for their incorporation into polymers is by coating technologies. [18,19] Once the essential oils are directly incorporated into the polymer matrix by high-temperature melt processing, antimicrobial activity is achieved. [16,18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33] However, this activity is evaluated, in most cases, immediately after film production, [29,[33][34][35] while the challenges associated with the controlled and prolonged activity of these films are not addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory panels evaluating medium-well roast beef samples coated with a chitosan solution formulated with LAE were able to identify the difference between treated and control samples immediately after surface coating treatments but not on day 15 (Wang et al, 2015). Similarly, Otero et al (2014) reported that polypropylene and polyethylene tetrephalate films coated with LAE did not significantly affect the organoleptic properties of Zamorano cheese slices. Therefore, chitosan solutions formulated with LAE may not negatively influence the organoleptic properties of cheese, but future studies are warranted.…”
Section: Antimicrobial Activity Of Chitosan Coating With Acslmentioning
confidence: 95%
“…Some commodity polymers such as low density polyethylene (LDPE) [22][23][24][25][26] , poly(vinyl chloride) (PVC) 22 and polypropylene (PP) [27][28][29] have been tested as adequate matrices to host different herb extracts. But in recent years biopolymers based on starch, cellulose derivatives, chitosan/chitin, gums, proteins obtained from animal or plant-sources, and lipids have emerged as environmentally-friendly alternatives to synthetic polymers as carriers of herb extracts (Table 1).…”
Section: Herbsmentioning
confidence: 99%